2010
DOI: 10.1149/1.3254165
|View full text |Cite
|
Sign up to set email alerts
|

Bis-(3-sodiumsulfopropyl disulfide) Decomposition with Cathodic Current Flowing in a Copper-Electroplating Bath

Abstract: The composition of the plating electrolyte is important in a copper (Cu) electroplating process. The consumption rate of bis(3-sodiumsulfopropyl disulfide) (SPS) has a strong correlation with the electroplating current density. The decomposition of SPS is relative to the electroplating charge and to the age of the Cu anode. The cathodic current density improves SPS breakdown, and it increases the generation of by-products resulting from SPS decomposition. The aged bath is examined using potentiodynamic polariz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
19
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 24 publications
0
19
0
Order By: Relevance
“…A large number of studies have reported degradation effects associated with interactions between Cu͑II͒/Cu͑I͒ and SPS 2− /MPS − in these types of cells. [8][9][10][11][12][13][14][15][16][17][18][19][20][21][22] At the same time, interactions with atmospheric O 2 and the reduction intermediate H 2 O 2 may also have a direct or indirect role in thiol/disulfide chemistry. 8,23 To investigate these inter- Table III. 4 2− x is equal to g g −1 .…”
Section: D180mentioning
confidence: 99%
“…A large number of studies have reported degradation effects associated with interactions between Cu͑II͒/Cu͑I͒ and SPS 2− /MPS − in these types of cells. [8][9][10][11][12][13][14][15][16][17][18][19][20][21][22] At the same time, interactions with atmospheric O 2 and the reduction intermediate H 2 O 2 may also have a direct or indirect role in thiol/disulfide chemistry. 8,23 To investigate these inter- Table III. 4 2− x is equal to g g −1 .…”
Section: D180mentioning
confidence: 99%
“…The additives exist in the form of complex, such as SPS-Cl --Cu 2+ . [2][11] The numerical simulation is based on the following assumptions: 1)additives are in the forms of accelerator complexes or inhibitor complexes in the electrolyte and these complexes are electropositive; 2)before the electrodeposition starts, adsorptions of the additives is completed and the adsorption process abides by the rule which is the strength of PEG adsorption is higher than the strength of SPS adsorption;3)there is only one species on the sites of electrode; 4)competing adsorption between SPS and PEG decides the concentration of additives; 5)electrodepostition velocity was decided to the surface coverage of the accelerator. The electrodeposition process is explained by this assumption.…”
Section: Numerical Modelmentioning
confidence: 99%
“…Commonly plating baths employed for Cu-electro-plating purposes have at least three or four components: a polyether such as poly (ethylene glycol) (PEG) or polyalkylene glycols, a sulfonate-terminated thiol or disulfide catalyst such as bis(3-sodiumsulfopropyl disulfide) (SPS) or NaSH(CH 2 ) 3 SO 3 (MPS), a halide ion such as chloride ions (Cl − ), and a nitrogen-based small molecule or polymer leveler. [2] Some numerical models of electrodepostion have been developed to explain the superfilling process. The CEAC mechanism model which exactly described the superfilling process of Dual-Damascene and CVD (chemical vapor deposition) was built by T.P.Moffat etc.…”
Section: Introductionmentioning
confidence: 99%
“…However, the electrodic activity of SPS is also important. 15,16 Based on the mass-spectrum data obtained by Hung et al 17 and West et al, 18 together with information from Atotech Inc., 19 SPS breakdown in a standard copper electrolytic bath may be summarized by Fig. 1, although more interconversions and other breakdown products were reported.…”
mentioning
confidence: 99%
“…Both pathways, however, may eventually lead to PDS, which has been shown to be the most stable byproduct of SPS decomposition. [16][17][18] The reduction of SPS to MPS has also been associated with the catalytic action of SPS through various hypothesized mechanisms, many involving stabilization of cuprous complexes at the electrode surface. [20][21][22][23][24][25][26] The ferric/ferrous redox couple is utilized in copper electrolytes for plating printed circuit boards, and has been considered for implementation in on-chip metallization of copper.…”
mentioning
confidence: 99%